1997
DOI: 10.1007/s100480050012
|View full text |Cite
|
Sign up to set email alerts
|

Muscle apoptosis in humans occurs in normal and denervated muscle, but not in myotonic dystrophy, dystrophinopathies or inflammatory disease

Abstract: Recent data suggest that death of muscle cells during development and in selected pathological conditions occurs via apoptosis. We investigated the occurrence of apoptosis in normal and pathological human skeletal muscle, using in situ end-labeling (ISEL) to detect DNA fragmentation, and immunohistochemistry for the expression of tissue transglutaminase and interleukin-1beta-converting enzyme (ICE)-like proteases. In normal subjects, apoptotic myonuclei were occasionally observed as evidence of normal tissue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 24 publications
2
32
0
1
Order By: Relevance
“…Bar, 10 m. young adult and aged quails. Previous findings have shown a role for apoptosis in muscle atrophy below the control muscle mass level induced by hindlimb suspension/unweighting, muscle denervation, and limb immobilization (1,8,17,27,28,37,48,54). In this study, we have demonstrated that apoptosis is also involved in unloading-induced muscle atrophy, in which muscle mass is reduced from a hypertrophied state to control levels.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Bar, 10 m. young adult and aged quails. Previous findings have shown a role for apoptosis in muscle atrophy below the control muscle mass level induced by hindlimb suspension/unweighting, muscle denervation, and limb immobilization (1,8,17,27,28,37,48,54). In this study, we have demonstrated that apoptosis is also involved in unloading-induced muscle atrophy, in which muscle mass is reduced from a hypertrophied state to control levels.…”
Section: Discussionsupporting
confidence: 59%
“…It has been commonly shown that muscle mass loss during disuse is associated with a decreased number of muscle nuclei (3-5, 25, 38); therefore, it is reasonable to suggest that muscle mass loss during muscle disuse is mediated by decreasing the nuclei number and thereby maintaining a homeostatic balance in the myonuclear domain (i.e., the cytoplasmic volume of myonuclei) in the multinucleated skeletal myocytes (3-5, 25, 38 -40). On the basis of the fact that apoptosis is consistently demonstrated during hindlimb suspension/unweighting, muscle denervation, and limb immobilization (1,8,17,27,28,37,48,54), it has been proposed that the loss in nuclei number could possibly be achieved through the activation of pathways resulting in apoptosis in the skeletal myocytes. Indeed, Allen et al (1) demonstrated that apoptosis is associated with the loss of muscle mass and myonuclei during hindlimb unweighting, because they found that TUNEL-positive nuclei increased in muscles after 14 days of unweighting.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, increased labelling for DNA breaks as indicated by transferase-mediated dUTP biotin nick-end labelling (TUNEL) and altered BCL-2 expression have been shown in skeletal muscle following denervation. 5,21,22,[44][45][46][47][48][49] By using mice that are deficient of the Bax gene, an upstream essential pro-apoptotic mediator, we provide further evidence supporting that apoptotic signalling has a significant role and may be involved in mediating muscle wasting during denervation. We have demonstrated that the extent of muscle loss following denervation is attenuated in the skeletal muscle of Bax −/− mice compared to wild-type animals.…”
Section: Discussionmentioning
confidence: 69%
“…3 Intriguingly, there is a growing body of evidence indicating that apoptosis may have a regulatory role in the denervation-associated pathologic muscle wasting. [4][5][6][7][8] Nevertheless, the importance of apoptosis in mediating muscle wasting in response to denervation remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported as a mechanism for removal of undesired myotubes (mononucleated cells) during development (Sandri and Carraro, 1999). Additionally, apoptotic death of single nuclei in otherwise normal muscle fibre has been shown with an incidence of 0.1% (Sandri et al, 1998) to 0.3% (Migheli et al, 1997) TUNEL-positive nuclei. Muscle satellite cells are believed to form a stable, self-renewing pool of stem cells in adult muscle, where they function in tissue growth and repair.…”
Section: Ascidians As a Model For Apoptosismentioning
confidence: 99%